Cuencos de deflexión 3d en pavimento flexible (2021)
When designing a flexible pavement construction model, it must meet the standards for allowable values and reserve percentages for stresses, strains, and deflections so that they can provide service during the design period. Deflection for being within the essential admissible criteria; It becomes an important study factor, so the objective of this article is the analysis of the effect and damage caused by traffic loads through load spectra, applying the elastic theory, determining and graphing the transversal and longitudinal deflection bowls in 2D and 3D. ; for a 3S1 configuration vehicle with maximum axle weights allowed by Colombian regulations and modeled in WinJULEA with a typical pavement structure to determine deflections in more than 600 points; analyzing the damage caused to the pavement where deflections greater than 1 mm were found as a result of the monotonic load of each axis and the interposition of deflection bulbs that create critical points where the pavement suffers damage similar to that found under the load plates.